2010
DOI: 10.1007/s10584-010-9950-2
|View full text |Cite
|
Sign up to set email alerts
|

Climate change features along the Brahmaputra Valley in the past 26 years and possible causes

Abstract: Through analyzing the changes of averaged temperature and precipitation along the Brahmaputra Valley from 1980 to 2005, and investigating the correlation between atmospheric circulation indices and these changes, the respondence of the Brahmaputra Valley to the global warming had been analyzed in this paper. It is found that the Brahmaputra Valley climate became warmer and wetter from 1980 to 2005, and the change magnitude is higher than that over the whole Tibetan Plateau. Therefore, the respondence of the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…The climate of YTR basin is dominated by the South Asia monsoon, which is the most prominent monsoon system of the world (Caesar et al, ; Dong et al, ; Song et al, ). As shown in Figure a, the precipitation exhibits clear seasonal variations under the influence of South Asia monsoon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate of YTR basin is dominated by the South Asia monsoon, which is the most prominent monsoon system of the world (Caesar et al, ; Dong et al, ; Song et al, ). As shown in Figure a, the precipitation exhibits clear seasonal variations under the influence of South Asia monsoon.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the value of ET and its uncertainty in 1998 are abnormal when compared with that in other years, which may be resulted by the huge difference between five ET products, but these have little influence in the estimation of total water basin discharge during the whole study period. The climate of YTR basin is dominated by the South Asia monsoon, which is the most prominent monsoon system of the world (Caesar et al, 2015;Dong et al, 2016;Song et al, 2011). As shown in Figure 7a, the precipitation exhibits clear seasonal variations under the influence of South Asia monsoon.…”
Section: Estimation Of Uncertainties In Precipitation and Etmentioning
confidence: 99%
“…The BRV lies between the southeast Tibetan Plateau and the Assam Hills of northeast India. Song and co‐workers [ Song et al , 2011] recently reported that the surface temperature in the BRV has been increasing at a rate of 0.03 K/year from 1980 to 2005. The magnitude of this temperature change is greater than that over the whole Tibetan Plateau, which has been identified as a major driver of the climate change in the northern hemisphere [ Feng et al , 1998; Pan and Li , 1996; Xu et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of this temperature change is greater than that over the whole Tibetan Plateau, which has been identified as a major driver of the climate change in the northern hemisphere [ Feng et al , 1998; Pan and Li , 1996; Xu et al , 2009]. Precipitation has also increased at a rate of 4 mm/year, and this increase has been attributed primarily to anomalous summer precipitation [ Song et al , 2011]. In this paper, we present the results of surface measurements of BC aerosol mass concentrations during the winter of 2011 at Guwahati, India, the largest metropolitan city in the BRV.…”
Section: Introductionmentioning
confidence: 99%
“…For the specific region of YZR and its two tributaries, previous studies focused on the analysis of the land-atmosphere interaction based on the in-situ measurements (e.g., You et al 2007;Song et al 2011). As for satellite remote sensing, many studies focused on the retrieval algorithms of land surface parameters (e.g., Zhong et al 2011a;Zhong et al 2012).…”
Section: Introductionmentioning
confidence: 99%